2013
DOI: 10.1007/s00374-013-0808-4
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface earthworm casts can be important soil microsites specifically influencing the growth of grassland plants

Abstract: Earthworms (Annelida: Oligochaeta) deposit several tons per hectare of casts enriched in nutrients and/or arbuscular mycorrhizal fungi (AMF) and create a spatial and temporal soil heterogeneity that can play a role in structuring plant communities. However, while we begin to understand the role of surface casts, it is still unclear to what extent plants utilize subsurface casts. We conducted a greenhouse experiment using large mesocosms (volume 45 l) to test whether (1) soil microsites consisting of earthworm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…Hence, some of the reported earthworm effects could also result from nutrient input caused by decomposing worm tissue rather than from actual earthworm activity. In previous experiments with the same substrate type and earthworm species, we documented earthworm activity throughout several months (Zaller et al 2013b ) with earthworm recovering rates of up to 93 % (Zaller et al 2011c ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Hence, some of the reported earthworm effects could also result from nutrient input caused by decomposing worm tissue rather than from actual earthworm activity. In previous experiments with the same substrate type and earthworm species, we documented earthworm activity throughout several months (Zaller et al 2013b ) with earthworm recovering rates of up to 93 % (Zaller et al 2011c ).…”
Section: Discussionmentioning
confidence: 87%
“…We observed a decline of earthworm biomass over the course of the experiment irrespective of AMF treatment. Some decline in earthworm biomass is frequently observed in earthworm laboratory studies, especially when experiments lasted several months (e.g., Wurst et al 2004b ; Zaller et al 2013b ). In the current study, we observed regular earthworm activity by surface castings until the end of the experiment; however, we did not quantify this activity and did not count the number of earthworms present at harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Pelosi et al 2014 ; Zaller et al 2014 ; Gaupp-Berghausen et al 2015 ; Travlos et al 2017 ). We explain the contrasting effects of the current study as follows: first, we measured earthworm activity by their surface cast production; however, it might well be that earthworms responded by changing their subsurface casting behaviour instead (Zaller et al 2013 ). Second, the herbicides were applied within grapevine rows only but not between rows leaving two-thirds of the area untreated.…”
Section: Discussionmentioning
confidence: 92%
“…Monitoring surface casting activity has recently been proposed as an ecotoxicity test better related to earthworms’ ecological role than standard laboratory tests 26 . Although the studied earthworm species differ in their feeding behavior, both have been shown to cast on the soil surface when foraging for leaf litter and other organic material 27 28 . The peak in surface casting activity observed after herbicide application was therefore likely the consequence of an increased availability of dead leaf material.…”
Section: Resultsmentioning
confidence: 99%